The food supply of the future - Broquet, Prudence Dell (My University, 1900)
Introduction: According to the hypothesis of Malthus, the population tends to increase in geometrical ratio, while the reproduction of food goes on by arithmetical ratio consequently there could not be enough food to supply the population, and death must come to the ones who were crowded out or who were least fitted to survive. But Malthus was a young man just returned from college when he wrote this book, and after discussing the question with his father around their fireside, and being severely attacked by the critics, he reconsidered the subject, and in a few years wrote another book, which exactly disputed the doctrine of the first. He did not say that he had disputed the arguments in the first work and what seems remarkable is that people did not find it out for several hundred years. Ricardo and others wrote of the diminishing returns of land; but this theory has as yet no apparent foundation, either in science or experience. Every year since these theories have been presented there has been a constant gain in the means of subsistence in proportion to the ratio of population. Modern science has proved that land is a mere instrument for the conversion of certain elements of nutrition from one form to another. The supply of energy which can thus be converted is immeasurable. Soil is not necessary for plant growth. Vegetation may be produced in water, with the proper temperature, certain elements of plant food in very small quantities, and the air will supply all other materials which are necessary to its perfect development. Its store is inexhaustible. Nature need not be depended on, for it has often been demonstrated that irrigation can make fertile otherwise barren regions, as Egypt, which would be a desert were it not for the annual overflow of the Nile. Irrigation in the United States may be accomplished by placing dams in the mountains and hills, which will hold the water that falls in winter till it is needed in spring and summer. By this means the dry part of the United States, where almost nothing is now raised, could be made to feed as dense a population as Italy or Spain.
Citation: Broquet, Prudence Dell. The food supply of the future. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Agriculture; Food Production; Food Supply; Nutrition; Irrigation; Theses